Controller optimization for a solar tracking system using differential evolution - Espitia Cuchango, Helbert Eduardo; Sierra Vargas, Fabio Emiro (TECCIENCIA, 2015)
This paper details the design and implementation of two analog controllers for the solar tracker located in the thermal power plant laboratory at the Universidad Nacional de Colombia. In this study we used differential evolution for the optimization of the controllers. In addition to the design of the controllers, it is possible with this approach to observe the characteristics of this bio-inspired algorithm. As a result, we first present the optimization process and subsequently the dynamic response of the controllers implemented.